Investigating the Implementation of Online Learning in Remote Learning Context - Nyudak, Dwi Tahamata; Putra, I Nyoman Adi Jaya; Santosa, Made Hery (LPPM Undiksha, 2021)
Covid-19 brings many changes in educational field especially on the role of ICT which is frequently used to support learning recently. However, even without this pandemic, teaching agents actually should slowly adjust the way learning is done since 21st century learning and industrial revolution 4.0 bold important point on the use of ICT for learning besides the 4Cs (Communication, Collaboration, Creativity and Critical thinking). This study aims to analyze teacher’s cognition towards online learning; the implementation of online learning; the consistency of teacher’s cognition and implementation of online learning; teacher’s perception toward online; students’ perception toward online learning; and parents’ perception toward online learning. In collecting the data, questionnaires, interview and observation checklist analysis were done. The result showed that the teacher had high cognition towards online learning; the teacher did several preparations and there were some procedures applied in online learning in remote learning context; teacher’s cognition and the implementation were consistent; the teacher perceived online learning positively; the students perceived online learning positively with some surprising information from the open-ended questionnaire which was in different side from the closed ended questionnaire; the parents perceived online learning in a balance view at first but the open-ended questionnaire stood on negative side.